A near-zero-waste approach using simple physical-chemical methods recovery high concentrations of ammonia nitrogen, heavy metal, and sodium salts from hazardous vanadium-extracted solution. (20th September 2021) - Zhou, Suying; Dong, Mengge; Ding, Xueyong; Xue, Xiangxin; Yang, He; Zhang, Xuefei
Abstract: An integrated simple physical-chemical method was proposed to realize the comprehensive utilization of valuable resources from vanadium-extracted solution. The hazardous vanadium-extracted solution contains high concentrations of Cr(VI), ammonia nitrogen, sodium salt, and silicic acid. Firstly, a series of operations include reduction-precipitation, calcination, and leaching were used to recover high concentration Cr(VI), and 99.96% of Cr(VI) was recovered as chromium oxide with the purity of 97.24%. Optimum conditions for the reduction pH, amount of sodium sulfite, precipitation pH, and precipitation time were 2.0, 1.2 times theoretical, 7.3, and 15 min, respectively. Secondly, clean ammonia nitrogen recovery through waste heat distillation was realized. And the total recovery efficiency of ammonia nitrogen was 95.6% at pH = 11.0, distillation 50 min with 0.5M sulfuric acid as the absorption liquid. Also, the distillation residue sodium sulfate was concentrated and purified by distillation. Finally, all the resources were separated efficiently and could be reused back into the upstream vanadium extraction process, achieving resource recycling. Moreover, material balance, energy analysis and the flow chart of the near-zero-waste approach for resource recycling from the hazardous vanadium-extracted solution were concluded. Graphical abstract: Image 1 Highlights: A near-zero-waste approach using simple physical-chemical methods was proposed. 99.96% of Cr(VI) was recovered in the form of Cr2 O3, with a purity of 97.24%. 95.6% of NH4 + -N was recycled by waste heat distillation. Material balance and energy analysis were provided. The flow chart for vanadium-extracted solution resource recycle was concluded.